DESAIN PRIMER MMP-8 dan IL-6 UNTUK ANALISIS EKSPRESI GEN JARINGAN GUSI Rattus norvegicus DENGAN qRT-PCR - Yasmine Dwinda; Muhammad Farikh; Vraya Tiranissa; Windi Yunita Sari; Bintang Fadhil Ramadhan; Siska Alicia Farma (Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2026)
Matrix Metalloproteinase 8 (MMP-8) and Interleukin 6 (IL-6) are two important genes that mediate inflammation and play a role in inflammatory cases. This study aims to design two specific primer candidates for testing gene expression using the qRT-PCR method in Rattus norvegicus experiencing inflammation and gingivitis. Primer design was performed using Geneious Prime software and BLAST primers to determine primer quality through PCR product size, primer length, melting temperature (Tm), and %GC, as well as to ensure that the resulting primers only bind to the Rattus norvegicus genome target. The results showed that the size of the MMP-8 forward product CGGGGTATTGGAGGAGATGC; reverse CAGGGTTGTCTGAAGGTCCATA was 241 bp with a primer length of 20-22 nucleotides, %GC between 50-60%, and Tm not more than 60°C, and the size of the IL-6 product forward AGAGACTTCCAGCCAGTTGC; reverse TGCCATTGCACAACTCTTTTC is 199 bp with a primer length of 20-21 nucleotides, %GC between 42.86-55% and Tm not more than 60°C. BLAST primer results indicate that both primer pairs are specific and suitable as candidate primers for qRT-PCR testing in studies of inflammation-related gene expression and gingival inflammation.